Regulasi emosi dan perilaku agresi siswa: Budaya kehormatan sebagai mediator: Emotion regulation and students' aggressive behavior: Honor culture as a mediator - Domino, Primus; Hanurawan, Fattah; Murwani, Fulgentius Danardana; Eva, Nur (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
This research aims to determine the role of honor culture in mediating emotional regulation and students' aggressive behavior at school. The research participants were 245 students at high schools in Manggarai Regency, Flores, NTT, Indonesia who were recruited using purposive judgment sampling techniques. Research data collection used an aggression behavior scale, an emotional regulation scale and a culture of honor scale. All scales have been validated using Confirmatory Factor Analysis (CFA). Data analysis used a mediation model regression, with the help of the SPSS For Windows 3.5.2 program. The research results show that honor culture plays a significant role in mediating the relationship between emotional regulation and students' aggressive behavior. Educators should empower a culture of honor to improve students' emotional regulation so that they do not behave aggressively at school.